RANCANG BANGUN SISTEM INFORMASI MUSYAWARAH PERENCANAAN PEMBANGUNAN PADA BADAN PERENCANAAN, PEMBANGUNAN, PENELITIAN DAN PENGEMBANGAN DAERAH KABUPATEN FAKFAK - Riyadh Arridha; Tomsio, Rusydi; Titing Magfirah (LPPM STMIK STIKOM Indonesia, 2019)
Development planning deliberations is an annual activity held by Badan Perencanaan, Pembangunan, Penelitian dan Pengembangan Daerah (BP4D). It is used to help government in regional development matters. It also helps to solve any problems occurred in regional development in order to bring welfare to the society. The implementation of information systems is required to optimize data tabulation and utilization. For instance, processing data from the results of planning deliberation which are taken from many parties, such as Bappeda and regional organizations. Further, the implementation of information systems in data processing is more efficient and modern. The result of the research is producing an information system to help regional development agency (BP4D) and regional organizations in processing and reporting the result of development planning deliberations. Furthermore, waterfall method with structured design is used in program system processing. Meanwhile, the testing method uses black box model. Then, the result of the test shows that the system has good performance.